Model Eko-epidemiologi dengan Waktu Tunda, Mangsa Panen dan Penambahan Secara Konstan Mangsa Rentan - Meiky Riani; Muhammad Subhan (Journal of Mathematics UNP, 2019)
Abstract – In this article discussed eco-epidemiological with time delay, harvesting prey and addition constally suspectible prey. Eco-epidemiological is study the spread of infectious diseases in population in the interaction in an environment. Eco-epidemiological will be analyzed by finding the stability of fixed point. The model consist of tree differential equations. In this model the population is diveded into three parts suspectible prey, infectious prey and predator. The model have four fixed points. Those are extinction , axial , infected prey extinction or disease free  and the coexistence between prey and predator .Keywords – Eco-epidemiological , Predator-prey,Time Delay,Fixed Point